Attention to detail: how do information users process exhibits in Form 10-K? - Cheng, Stephanie F.; Li, Yimeng; Lin, Pengkai (Review of Accounting Studies, 2026)
Abstract Form 10-K offers a setting for studying how users process complex, multi-layered disclosures: managerial narratives in the main file alongside separate exhibits, such as contracts and certifications, that provide unfiltered detail. Drawing on rational inattention theory, we investigate how users allocate limited attention across these components. Users typically begin with the main file and selectively access exhibits when the main file appears shorter, less readable, or less confident, indicating higher perceived information loss. This pattern strengthens for exhibits that offer more detail on topics discussed in the main file and among institutional investors and time-constrained users. Exhibit access persists beyond the initial filing window and increases around subsequent firm events, especially when external monitoring strengthens and event-related information asymmetry grows. Collectively, our findings underscore the active, discerning nature of user attention in navigating multi-layered disclosures and reveal the often-overlooked informational value of exhibits in Form 10-K.